A Regional Analysis of Supply Chain Management in India’s Defense Sector: The Case of Gwalior, Madhya Pradesh - Sharma, Sandeep; Chaurasiya, Ravi; Mohite, Rohit; Akre, Sandesh (Indo Consultan Energi, 2025)
Effective supply chain management (SCM) is crucial for India's defense sector to ensure operational readiness and national security. However, persistent challenges in inventory control and logistics coordination continue to impact efficiency. This study examines the supply chain management (SCM) dynamics in Gwalior, Madhya Pradesh, which holds strategic potential due to industrial zones such as Malanpur and Banmore. Despite this, local contribution to defense procurement remains limited, as evident in the Jabalpur Vehicle Plant's sourcing of only 10% of components from state vendors—primarily due to technological and quality constraints. Through field interviews, surveys, and stakeholder consultations, the research identifies critical factors influencing supply chain management (SCM) performance, including technology adoption, infrastructure readiness, and quality compliance. The study highlights the potential of local micro, small, and medium enterprises (MSMEs) to enhance their capabilities by leveraging national initiatives such as